(-2, 6) is a solution of [tex]x+\frac{1}{2} y=1[/tex]
Step-by-step explanation:
Given equation:
[tex]x+\frac{1}{2} y=1[/tex]
Case1: substitute the points (-2, 6) in the given equation, we have,
=> [tex]x+\frac{1}{2} y=1[/tex]
=> [tex](-2)+\frac{1}{2}\times(6)=1[/tex]
=> [tex](-2)+\frac{6}{2}=1[/tex]
=> [tex]-2+3=1[/tex]
=> [tex]1=1[/tex]
Case2 : substitute the points (2, -6) in the given equation, we have,
=> [tex]x+\frac{1}{2} y=1[/tex]
=> [tex](2)+\frac{1}{2}\times(-6)=1[/tex]
=> [tex](2)+\frac{-6}{2}=1[/tex]
=> [tex]2-3=1[/tex]
=> [tex]-1\neq1[/tex]
Case 3: substitute the points (-2, -6) in the given equation, we have,
=> [tex]x+\frac{1}{2} y=1[/tex]
=> [tex](-2)+\frac{1}{2}\times(-6)=1[/tex]
=> [tex](-2)+\frac{-6}{2}=1[/tex]
=> [tex]-2-3=1[/tex]
=> [tex]-5=1[/tex]
=> [tex]-5\neq1[/tex]